Practical neurology visual review - Biller, José (Wolters Kluwer Health, Lippincott Williams & Wilkins, 2013)
Now in a fully revised and updated Second Edition, Practical Neurology Visual Reviewpreviously known as (Practical Neurology DVD Review) continues to be a powerful educational tool for mastering the clinical practice of neurologic diagnosis. The book opens new venues for teaching and learning the essentials of neurology by utilizing an interactive patient-based audiovisual electronic format.